KONTRIBUSI PLTU PAITON DALAM PEMBANGUNAN EKONOMI MASYARAKAT PROBOLINGGO DARI PERSPEKTIF ISLAM - M. Hibatullah Huwaidi; Shafwan Tsauri (AL-MUJADDID - JURNAL EKONOMI DAN BISNIS ISLAM, 2025)
The purpose of this article is to look at the contribution of the Paiton Steam Power Plant (PLTU) in the economic development of society in Probolinggo, East Java from an Islamic perspective. PLTU Paiton is one of the largest power plants in Indonesia and plays an important role in meeting electricity needs in the region. In an Islamic perspective, corporate social responsibility is a moral obligation for companies to provide benefits to the surrounding community and maintain environmental sustainability. This article finds that the Paiton PLTU has had a positive impact on the community's economy through various things such as increasing employment opportunities, community income, and infrastructure development. Therefore, PLTU Paiton must manage the waste and emissions produced so that they do not damage the surrounding environment.